Vaccination timeliness and delay in low- and middle-income countries: a systematic review of the literature, 2007-2017 - Nina B. Masters; Abram L. Wagner; Matthew L. Boulton (Taylor & Francis Group, 2019)
Background: Traditional measurements of vaccine coverage at specific ages can mask poor vaccine timeliness. However, optimal measurement of timing is unclear due to variations in countries' recommended vaccination schedules and lack of a commonly accepted standard for "timeliness". We conducted a systematic review of literature on vaccine timeliness and delay in low- and middle-income countries from 2007 to 2017. Methods: A search of articles published between January 1 2007 and December 31 2017, was performed in PubMed, EBSCOhost, and Embase. Results: 67 papers were included, of which 83% used a categorical measure of delay and 41% evaluated continuous delay. The most common age at assessment was 1 month, with earlier age benchmarks typically used with birth doses. Conclusions: Categorical definitions of vaccination timing vary widely, with benchmarks of delay varying from days to weeks to months. Use of a continuous measure of vaccine delay may be more informative and comparable.